A comparison of trust and reciprocity between France and Germany: Experimental investigation based on the investment game - Willinger, Marc; Keser, Claudia; Lohmann, Christopher; Usunier, Jean-Claude (Journal of economic psychology, 2003)
We compare the results of a one-shot investment game, studied earlier by Berg et al. [Games and Economic Behavior 10 (1995) 122], for France and Germany. In this game, player A is the trustor and player B the trustee. The average level of investment is significantly larger in Germany, but the level of reciprocity is not significantly different between the two countries. This implies that German B-players earned significantly more than French B-players. Furthermore, in both countries B-players earned significantly more than A-players. Our results support Fukuyama’s conjecture that the level of trust is higher in Germany than in France, a situation which can explain a higher rate of investment and a higher level of performance. However, our results also show that the increased revenue which is attributable to the higher level of trust, is not shared in a more equitable way, but essentially increases B-players’ payoffs. Finally, based on an intercultural trust experiment, we show that French A subjects did not find German B subjects less trustworthy and German A subjects did not find French B subjects less trustworthy.